The effect of two different doses of dexmedetomidine to attenuate cardiovascular and airway responses to tracheal extubation: a double blind randomized controlled trial - Antony, Deepu; C V, Davies; Koshi Thomas, Mariam; Shenoy, Usha; V, Mahesh; Kochuthresia J, Puthumana (International Journal of Medical Research and Review, 2016)
Background: The objective of the study is to assess the effectiveness of two different doses of dexmedetomidine, an alpha 2 adrenergic agonist, to attenuate the cardiovascular and airway responses to tracheal extubation and to observe the adverse effects. Methodology: Ninety ASA grade I and II patients aged 18-50 years were randomized into three groups; A, B, and C to receive dexmedetomidine 0.5µg/kg, 1µg/kg and normal saline placebo respectively about 15 minutes before discontinuation of inhalational agent. The heart rate, systolic blood pressure, diastolic blood pressure and mean arterial pressure were recorded during administration of drug, before extubation, during extubation, at 1, 3 minutes and every 5 minutes thereafter. Extubation quality was assessed on a 5 point scale and sedation by Ramsay sedation score. Results: There was significant decrease in heart rate and mean arterial pressure (p<0.001) during extubation in group A and B. Ninety percent of patients in group A, 93.3% patients in group B and 16.7% in group C could be extubated smoothly. The average time to extubate was 12.13±2.11, 14.08±3.19 and 10.27±2.09 minutes in groups A, B, and C respectively (P value <0.001). Higher incidence of bradycardia (p<0.001) was observed in Group A and B whereas incidence of breath holding was higher in group C (p=0.024). Conclusion: A dose of 0.5µg/kg of dexmedetomidine administered as a bolus infusion before extubation attenuates the stress response to extubation as effectively as 1µg/kg. Higher sedation scores and longer time to extubate are seen with a dose of 1µg/kg without causing respiratory depression.